2010
DOI: 10.1186/1755-7682-3-30
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of combination allogeneic stem cell therapy for spinal cord injury: a case report

Abstract: Cellular therapy for spinal cord injury (SCI) is overviewed focusing on bone marrow mononuclear cells, olfactory ensheathing cells, and mesenchymal stem cells. A case is made for the possibility of combining cell types, as well as for allogeneic use. We report the case of 29 year old male who suffered a crush fracture of the L1 vertebral body, lacking lower sensorimotor function, being a score A on the ASIA scale. Stem cell therapy comprised of intrathecal administration of allogeneic umbilical cord blood ex-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 109 publications
0
62
2
1
Order By: Relevance
“…24 It is also possible to use these cells for allogenic transplantation as there is little risk of immunological rejection or graft-versus-host reactions. 25 The safety of transplanted unmanipulated autologous bone marrow in subjects with SCI has been reported by Sykova et al 26 However, the authors could not confirm that the observed beneficial effects were due to cellular intervention. 26 Other groups have transplanted enriched or expanded bone marrow mesenchymal stem cells in SCI subjects either alone or in combination with CD34+ cells or GM-CSF.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…24 It is also possible to use these cells for allogenic transplantation as there is little risk of immunological rejection or graft-versus-host reactions. 25 The safety of transplanted unmanipulated autologous bone marrow in subjects with SCI has been reported by Sykova et al 26 However, the authors could not confirm that the observed beneficial effects were due to cellular intervention. 26 Other groups have transplanted enriched or expanded bone marrow mesenchymal stem cells in SCI subjects either alone or in combination with CD34+ cells or GM-CSF.…”
Section: Discussioncontrasting
confidence: 41%
“…26 Other groups have transplanted enriched or expanded bone marrow mesenchymal stem cells in SCI subjects either alone or in combination with CD34+ cells or GM-CSF. 21,25 However, because of various limitations of these studies, the outcomes reported are inconclusive. 2 This study was initially planned to transplant the Ficoll-purified mononuclear cell population as used in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Mackay-Sim et al 55 have used a single intraoperative injection. However, other authors 56,57 have performed cellular transplantation in three cycles; in each cycle, five intrathecal injections have been given at 2-11-day intervals. A fourth unresolved issue is whether to obtain stem cells from patients with spinal cord injury or from healthy volunteers.…”
Section: Amr Et Al Bridging Defects With Nerve Grafts and Stem Cellsmentioning
confidence: 99%
“…In a case report, Ichim et al 11 transplanted a combination of CD34 and placenta-derived MSCs intrathecally into a 29-year-old man with ASIA Grade A SCI after a plane crash. Serial transplantations were performed and were observed to subsequently lead to an improvement in ASIA grade (from Grade A to D) and neuropathic pain (10/10 to 3/10 consistently) over a 1-year follow-up period.…”
Section: Spinal Cord Injurymentioning
confidence: 99%